Authority – theory and experiment. Bocheński versus Milgram - Sękowski, Piotr (Hybris, 2012)
The article presents a conception of authority by Bocheński and the Milgram’s experiment in study of the obedience to authority. The essential problem is double - firstly it is attempt of answering the question: do we really have a deal with authority in Milgram’s experiment? If so, what kind of authority is it? – from the other hand it is the verification of Bocheński’s theory; how does it function in the concrete case.